OPTIMALISASI BIROKRASI DALAM PEMBANGUNAN EKONOMI: UPAYA MENYEDIAKAN KESEJAHTERAAN MASYARAKAT DI INDONESIA - Mochammad Iqbal Fadhlurrohman; Etika Khairina; Yagus Triana HS; Gugun Geusan Akbar (Universitas Djuanda Bogor, 2023)
This study aims to see how the government optimizes bureaucratic performance to help economic development and social welfare. The purpose of the bureaucracy in carrying out public services is to provide better services to the community so that people are happy with the services provided by the government. The process of economic development requires an efficient bureaucracy to maintain coordination between the government and the parties involved. In an effort to encourage community economic growth, the government must also carry out the process of making bureaucratic policies such as efficient socialization of programs. This study uses a qualitative analysis method with triangulation data analysis to make it easier to see the data. Based on the results of the analysis of this study, it seems that the government has streamlined the bureaucracy well. However, there are still problems in the bureaucratic process, as seen from the number of economies that grow from year to year, but this growth is unstable in the process of bureaucratic services carried out by the government, such as the high number of MSMEs in Indonesia.